SUCH FORMS AND METHODS OF MOTIVATION OF PRACTITIONERS IN THE SPHERE OF YOUR EDUCATION - KOZYNETS, Anatolii; SHPILEVA, Vira (Herald of Khmelnytskyi National University. Economic sciences, 2023)
In the minds of the current development of the practice of the sphere of general education and the strategic resources of the functioning of the foundations of education. Efficient management of specific resources favors the development of mortgages and increases the level of their competitiveness in the field of lighting services. Looking at the main mechanism of stimulation, it is not institutional interests, but the consumption of practitioners, as a destructive force, the development of laying the foundation for higher education. In today’s conscientious minds, the main direct motivational activity is not less than the achievement of high productivity of practice, but the activation of the creative potential of practical workers in the field of higher education. Therefore, it is necessary to appoint such a form and method of stimulation, as to be aware of the effectiveness of the promotion and support new trends in the scientific and lighting process and personnel management. The purpose of the study is research, generalization and development of theoretical and methodological approaches to the development of modern forms and methods of motivating employees in the field of higher education. Modern systems and methods of employee motivation must be combined with established principles to create a system focused on higher education. These systems should include forms and methods of motivation that are compatible with the modern world to encourage workers through short-term international projects. This should increase the number of workers with creative and educated backgrounds who stay in the industry for many years. Increasing creativity and scientific activity of employees will also make higher education systems more competitive and increase their overall quality. A necessary condition for the implementation of material forms of motivation is the availability of financial resources for their provision. The methods of direct material influence include the payment of salaries, as well as additional payments and allowances, to scientific and pedagogical workers in the field of higher education. The use of material methods will contribute to the financial support of employees and the improvement of the socio-economic situation of their families. The use of non-material methods has a psychological effect on the individual, acts as a mechanism for self-realization, scientific and creative development, implementation of developed ideas in scientific, educational and practical activities, which will contribute to the self-realization of employees in a higher educational institution. The functioning of the system of motivation of employees in the field of higher education should be comprehensive, as it combines not only the employment of a highly qualified employee for a vacant position and the signing of a long-term contract with him, but also the provision of conditions for the employee’s work so that he does not have to prematurely terminate the contract. When implementing forms and methods of work motivation, it is important to ensure a systematic process of interaction between management and employees. In addition to the external results of the applied motivation methods, which are manifested in the increase in the number and quality of scientific works, receiving honors, awards, etc., it is important to analyze the attitude of employees to the current system. It is expedient to regularly and periodically survey the employees of a higher educational institution regarding the positive and negative features of the motivation system and suggestions for its improvement. To operate effectively, higher education institutions need employees with a wide range of skills. Ensuring that these employees receive the proper care and attention from their supervisors is vital to the success of the institution. The success of these schools motivates staff to develop new ideas and improve higher education services. This creates a competitive advantage for these schools over other educational institutions. Now, motivational activity occupies a central place in our society. They activate the use of creative potential of employees and increase labor productivity. They must be defined and implemented in such a way as to meet the latest trends in higher education and personnel management..